ANALISIS PENGARUH GAYA HIDUP, LINGKUNGAN SOSIAL DAN LITERASI KEUANGAN SYARIAH TERHADAP PERENCANAAN KEUANGAN GENERASI Z MUSLIM DI JABODETABEK - Saniatun Nurhasanah; Aprilia Nabela Kesuma (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2023)
This research is a renewal from previous research which combines variables from several studies with different objects, namely the z generation of Muslims in the Jabodetabek area. This study aims to determine whether factors such as lifestyle, social environment and Islamic financial literacy affect financial planning carried out by generation z who are already working and living in the Jabodetabek area. This research uses a quantitative approach and uses structural equation modeling (PLS-SEM) as a data analysis method. Data acquisition is obtained by distributing questionnaires in the form of google forms to generation z, especially those who are already working and domiciled in the Jabodetabek area. This study gives the results that: (1) lifestyle factors have a positive and significant effect on financial planning, (2) social environment factors have a positive and significant effect on financial planning, and (3) Islamic financial literacy factors have a positive and significant effect on financial planning the z generation of Muslims in the Jabodetabek area.